Morphometrics of IPB D1, IPB D2 and IPB D3 Chickens Aged 4 to 12 Weeks at Sinar Harapan Farm Sukabumi - M. A. Rizqi; C. Sumantri; S. Darwati (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Research on the 11 morphometrics of IPB-D chicken in Sukabumi district has not been conducted. This study aimed to evaluate the morphometrics of IPB D1, IPB D2 and IPB D3 chickens in Sukabumi District. The design of this study was a completely randomized design with 3 levels of treatment linesnamely IPB D1, IPB D2 and IPB D3 with 95% confidence interval. Treatments that had a significant effect were followed by the Tukey test. Measured morphometric parameters such as shank length, shank circumference, femur length, tibia length, breast length, breast width, breast depth, breast circumference and back length. IPB D3 chickens show that their genetic condition is not yet stable as meat type. At the age of 4 to 8 weeks, IPB-D3 chickens have a larger size in the variables of shank circumference, femur length, tibia length, breast length and breast circumference. However, at the age of 8 to 12 weeks IPB-D3 chickens have a smaller size in the variables of breast length, breast width, breast depth, breast circumference and back length. Meanwhile, IPB D1 chickens show that they are genetically stable and IPB D2 is able to adapt because of its resistance traits.